One-Pot Synthesis of 7-Alkyl-6H,7H-naphtho[1’,2’:5,6]pyrano[3,2-c]chromen-6-ones in Presence of Alum - Xie, Youhai; Wang, Yingling; Wu, Liqiang (Asian Journal of Chemistry, 2011)
A simple, green and efficient solvent-free procedure for the synthesis of 7-alkyl-6H,7Hnaphtho[ 1',2': 5,6]pyrano[3,2-c]chromen-6-ones, from aldehydes, β-naphthol and 4- hydroxycoumarin in presence of alum at 120 ºC was described.